Pelatihan Pembuatan Kompos Sampah Organik Rumah Tangga di Kota Malang - Saputra, Rafael Leo; Widowati, Widowati; Noorvy, Dian; Wilujeng, Retno (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
The management of household waste, particularly organic waste, has emerged as a significant issue in RT 04 RW 06, Merjosari Village, Malang City. Over 50% of the total waste generated consists of organic materials. If not properly managed, organic waste can lead to environmental pollution and exacerbate health problems.This community service initiative aims to enhance public awareness and knowledge, especially among the local PKK mothers, regarding the management of organic waste through composting. The methods employed include site surveys, problem identification, coordination with relevant stakeholders, practical training on compost production, and demonstrations on using bioactivators to accelerate the composting process.The anticipated outcomes of this initiative include a reduction in the volume of unmanaged organic waste, improved soil fertility, and a decrease in negative environmental impacts. Through this training, it is hoped that the community will be better equipped to manage organic waste in a more effective and sustainable manner, ultimately fostering a cleaner and healthier environment.